Perlindungan Hukum Terhadap Pemegang Hak Guna Bangunan dari Tindak Kejahatan Pemalsuan Surat - Bayuadi, Muhammad Bimantoro; Sutedja, Bambang (Jurnal Ilmiah Wahana Pendidikan, 2024)
Abstract Land ownership often creates disputes, which can even lead to land grabbing or expropriation. The aim of writing this research is to understand the form of legal protection for holders of land certificates and what forms of document forgery. This study uses a normative juridical method.There are seven forms of letter forgery. In this case, the subject matter of Land Ownership Certificates can be found in Government Regulation Number 24 of 1997 concerning Land Registration, Minister of Agrarian Regulations/Head of BPN Number 3 of 1997 and Service Procedure Standards stipulated by the Head of BPN number 1 of 2010. Falsification of land ownership certificates often becomes a legal issue for irresponsible individuals or individual agencies or organizations. Key words: Legal Protection, Forgery, Land